MELUKISKAN AKUNTANSI DENGAN KUAS INTERPRETIF - Nurhayati, Nurhayati (BISNIS, 2015)
This  study  departs  from  the  domination  of  accounting  studies  using the   paradigm   of   positivistic   methodology.   The   aim   in   this studyprovides  an  alternative  approach  in  developing  interpretive  accounting research.  Triyuwono  (2013)  says  there  are  five paradigms  in  the  social sciences:   positivism,   interpretivism,   criticism   postmodernism,   and spiritualists.    Interpretivis    paradigm,    critical,    postmodernist    and spiritualists  using  qualitative  methods,  which  is  the  development  of positivistic paradigm. This paradigm is not mutually exclusive, ideally an accounting  researchers  must  be  able to  accept this  paradigm, called“multiparadigma”  (Triyuwono,  2013).  Interpretive  considers  that  truth, reality or real  life  does not have a one-sided,  but it has many  facets, can be  examined from  various  viewpoints.  Design  research  in  interpretive research,  phenomenology,  ethnography, ethnometodology,  narrative, case studies, and grounded theory.